2007
DOI: 10.1542/peds.2006-1726
|View full text |Cite
|
Sign up to set email alerts
|

Low-Income Uninsured Children With Special Health Care Needs: Why Aren't They Enrolled in Public Health Insurance Programs?

Abstract: Understanding why uninsured children with special health care needs do not participate in public programs is important, because these programs have the potential to cover almost all of this population. Initiatives to increase enrollment should yield real dividends given that the vast majority of low-income uninsured children with special health care needs have parents who say they would enroll their children in public coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 13 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…The complexity of the application process can also be a barrier. A survey of parents indicated that although 93.5% had heard of the insurance programmes for their children, only 48.1% thought the application processes were easy (Haley 2007). In addition, the requirement for applicants for health insurance to travel to enrolment sites has proved to be a constraint for families in rural or isolated places (Langwell 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of the application process can also be a barrier. A survey of parents indicated that although 93.5% had heard of the insurance programmes for their children, only 48.1% thought the application processes were easy (Haley 2007). In addition, the requirement for applicants for health insurance to travel to enrolment sites has proved to be a constraint for families in rural or isolated places (Langwell 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Thus, retaining coverage for children who enroll in Medicaid or CHIP is critical to ensuring their continuous access to care. 16,17 Research evidence suggests that many children who disenroll from public coverage become uninsured. 18,19 Thus, by retaining children in Medicaid/CHIP for longer periods of time, states are likely to also reduce the number of uninsured children.…”
Section: Methodsmentioning
confidence: 99%
“…One study revealed 52 barriers to enrollment comprising 11 domains, including lack of knowledge about Medicaid/CHIP, failure to apply, language barriers, immigration status, income, income verification, misinformation from insurance representatives, system problems, hassles, decisions that were still pending, and family mobility [8]. Multiple studies document that lack of knowledge about the Medicaid and CHIP programs is one of the most important barriers to enrolling eligible uninsured children [8,9,10,11,12,13]. A Kaiser Commission on Medicaid and the Uninsured study [9] found that only 26% of parents of eligible uninsured children said that they had ever talked to someone or received information about Medicaid enrollment, and another study [7] revealed that 27% of parents of uninsured eligible children had not heard of Medicaid or CHIP.…”
Section: Introductionmentioning
confidence: 99%
“…A Kaiser Commission on Medicaid and the Uninsured study [9] found that only 26% of parents of eligible uninsured children said that they had ever talked to someone or received information about Medicaid enrollment, and another study [7] revealed that 27% of parents of uninsured eligible children had not heard of Medicaid or CHIP. Hassles (i.e., a burdensome enrollment process) also have been identified in several studies as an enrollment barrier [8–13,14]; other recurrent enrollment barriers include language barriers [7–9;13], income and income verification [810], and mobility [8,12]. …”
Section: Introductionmentioning
confidence: 99%